English Language Proficiency and Early School Attainment Among Children Learning English as an Additional Language. Issue 3 (20th September 2016) - Whiteside, Katie E.; Gooch, Debbie; Norbury, Courtenay F.
Abstract : Children learning English as an additional language (EAL) often experience lower academic attainment than monolingual peers. In this study, teachers provided ratings of English language proficiency and social, emotional, and behavioral functioning for 782 children with EAL and 6, 485 monolingual children in reception year (ages 4–5). Academic attainment was assessed in reception and Year 2 (ages 6–7). Relative to monolingual peers with comparable English language proficiency, children with EAL displayed fewer social, emotional, and behavioral difficulties in reception, were equally likely to meet curriculum targets in reception, and were more likely to meet targets in Year 2. Academic attainment and social, emotional, and behavioral functioning in children with EAL are associated with English language proficiency at school entry.